Predictors of the incidence of respiratory tract infections in children under five years of age in urban areas: Evidence from Indonesia - Riyanto Riyanto; Herlina Herlina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Acute respiratory infection (ARI) remains one of the leading causes of morbidity and mortality among children under five, particularly in urban areas of low- and middle-income countries. This study purpose to identify the predictors of ARI incidence associated with household tobacco smoke exposure, neonatal asphyxia history, and exclusive breastfeeding practices among children under five years of age in an urban setting in Indonesia. A case–control study was conducted involving 88 children under five years (44 cases and 44 controls) recruited from urban public health centers. Data on risk factors were obtained through structured interviews and validated medical records. Multiple logistic regression analysis was employed to estimate adjusted odds ratios (AOR) and 95% confidence intervals (CI). Multivariate analysis revealed that two variables were significantly associated with ARI incidence: household exposure to tobacco smoke (AOR = 11.53; 95% CI: 3.46–38.41) and a history of neonatal asphyxia (AOR = 4.78; 95% CI: 1.05–21.86). Exclusive breastfeeding had a protective effect, reducing ARI risk by approximately twofold (COR = 2.19; 95% CI: 1.73–2.78). The model demonstrated good fit based on the Hosmer–Lemeshow test (p > 0.05). Household tobacco smoke exposure and neonatal asphyxia substantially increase the risk of ARI among urban children under five years of age , whereas exclusive breastfeeding serves as a strong protective factor. These findings underscore the importance of strengthening promotive–preventive interventions targeting household air pollution, neonatal care, and breastfeeding promotion in urban health policy frameworks.